Reinterpretation of Polygamy Verses Through Ibn ʿᾹshūr 's Maqāṣid al-Sharīʿah Theory - Ahmad Anas (The Ulama Cadre Education Program of Great Mosques of Istiqlal (PKUMI), 2025)
This study reinterprets Quranic verses on polygamy (specifically QS An-Nisā’:3) through Ibn ʿᾹshūr’s maqāṣid al-sharīʿah theory to address accusations of gender bias in Islam. Employing descriptive qualitative methodology and content analysis, it critically examines classical and contextual interpretations that either rigidly adhere to textualism or overemphasize socio-historical contexts, both deemed insufficient for resolving contemporary gender critiques. Ibn ʿᾹshūr’s approach presented as a moderate, universal framework minimizing juristic discord and blind fanaticism—reveals three key insights: First, the verse intrinsically links to preceding orphan-protection contexts, with polygamy framed as an emergency solution to prevent adultery (zinā) amid social vulnerabilities. Second, polygamy’s permissibility carries stringent, non-negotiable conditions of material and relational justice (e.g., separate residences, equitable financial support), rendering it practically arduous and contextually restricted. Third, asymmetrical rulings—permitting polygamy but prohibiting polyandry are justified through fiqh al-awlawiyāt (prioritization jurisprudence): polygamy’s micro-level harms ( jealousy) are outweighed by its macro-level benefits ( lineage preservation, disease prevention), while polyandry’s irreversible harms (lineage confusion, disease proliferation) exceed its potential benefits. The study concludes that Ibn ‘Āsyūr’s theory offers a balanced, gender-neutral exegesis by harmonizing textual fidelity with contextual maṣlaḥah (public interest), positioning polygamy as a last-resort safeguard rather than an unconditional right. This approach is advocated for reinterpretations of other contested Islamic legal verses.